Dsadvisor: A Tool to Support Predictive Tasks in Data Science - Câmara Filho, José Augusto; Monteiro, José Maria (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2021: Anais Estendidos do XXXVI Simpósio Brasileiro de Bancos de Dados, 2021)
Currently, professionals from the most diverse areas of knowledge need to explore their data repositories in order to extract knowledge and create new products or services. Several tools have been proposed in order to facilitate the tasks involved in the Data Science lifecycle. However, such tools require their users to have specific (and deep) knowledge in different areas of Computing and Statistics, making their use practically unfeasible for non-specialist professionals in data science. In this paper, we propose a tool, which aims to encourage non-expert users to build machine learning models to solve predictive tasks, extracting knowledge from their own data repositories. More specifically, DSAdvisor these professionals in predictive tasks involving regression and classification